Pelatihan Internet of Things (IoT) untuk Smart Home dan Smart School di SMK Garuda Nusantara - Danny, Muhtajuddin; Arwan Sulaeman, Asep; Maringan Hutauruk, Basar; Damuri, Amat (VINICHO MEDIA PUBLISINDO, 2025)
The rapid development of digital technology, particularly the Internet of Things (IoT), requires vocational education institutions to align graduate competencies with the demands of Industry 4.0. SMK Garuda Nusantara has significant potential in developing technology-based human resources; however, limitations remain in teachers’ and students’ practical IoT skills as well as in the availability of supporting learning facilities. This community service program aims to enhance teachers’ and students’ competencies through IoT training integrated with smart home and smart school concepts. The implementation method consists of preparation, socialization, theoretical training, hands-on workshops, mentoring, and program evaluation. The training focuses on the use of microcontrollers, sensors, and the development of applied IoT prototypes such as automatic lighting systems, RFID-based attendance systems, and classroom environmental monitoring. The expected outcomes include improved practical skills of teachers and students, the development of IoT learning modules based on project-based learning, and the creation of simple smart home and smart school prototypes applicable in the school environment. This program also supports the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) policy and contributes to the achievement of higher education Key Performance Indicators (IKU) through sustainable collaboration between universities and school partners.